Bench, bedside, boardroom: negotiating translational gene therapy. Issue 1 (2nd January 2017) - Addison, Courtney
Abstract : This article presents ethnographic material from a London-based group of gene therapists who received the opportunity to trial a device that, its makers claimed, would expedite and improve their cell work. The Vanguard cell processor elicits both enthusiasm and ambivalence from group members, which I seek to understand by examining the group's current manner of working alongside the device and its purported virtues. I show that cell processing currently involves complex practices of recognition, attention, care, and involvement, which answer to both the liveliness of cells and the experimentality of gene therapy. I read these practices as a well-honed configuration of productive engagements and detachments, which the Vanguard would thoroughly rearticulate. I thus argue that translational gene therapy is a site at which private and academic interests meet, and that translation more generally might be seen as a space where the relational format of science is renegotiated.